Effect of Papaya Decoction (Papaya Carica L.) on Increasing Breast Milk Production in Breastfeeding Mothers - Pebrianthy, Lola; Lubis, Mutia Sari; Maisyaroh, Yusnina (PT Inovasi Pratama Internasional, 2022)
Breastfeeding in postpartum mothers often encounter obstacles due to late release of breast milk or less milk production. Efforts to improve the nutrition of nursing mothers by providing nutrient-rich foods that can stimulate milk production, namely papaya fruit stew. This study aims to determine the effect of boiled papaya on increasing breast milk production. This research was conducted at the Independent Midwife Nelly Harahap Panyanggar, North Padangsidimpuan District on 27 breastfeeding mothers. Analysis of the data used is the Wilcoxon test. The results of this study showed the p-value = 0.001, (p <0.05). The conclusion is that there is an effect of papaya decoction on increasing breast milk production in breastfeeding mothers in the Independent Practice of Midwife Nelly Harahap, Panyanggar, North Padangsidimpuan District in 2021. Suggestions are expected for breastfeeding mothers to improve their understanding of breast care and the benefits of consuming boiled papaya fruit regularly so that milk production remains increased so that mothers can exclusively breastfeed.